أثر مخاطر التضخم على ربحية البنوك الإسلامية الأردنية - شواقفة, جورج ناصر (جامعة الوادي - University of Eloued, 2022)
هدفت الدراسة الحالية إلى بيان أثر مخاطر التضخم على ربحية البنوك الإسلامية الأردنية, وقد استخدمت الدراسة المنهج الوصفي التحليلي والمنهج القياسي كدراسة استقصائية على البنوك الإسلامية الأردنية خلال الفترة 2015-2019, باستخدام تحليل الانحدار الخطي والمتعدد وتحليل الارتباط واختبارات الدلالة. أجريت الدراسة على جميع البنوك الإسلامية الأردنية وعددها ثلاث بنوك (البنك الإسلامي الأردني للتمويل والاستثمار, والبنك الإسلامي العربي الدولي, وبنك صفوة الإسلامي). لتحقيق هدف الدراسة تم اعتماد مؤشر متوسط معدل التضخم كمتغير مستقل ومؤشر العائد على حقوق الملكية لقياس الربحية (ROE) كمتغير تابع, واعتماد مؤشر السيولة والرافعة المالية والقوة السوقية وحجم البنك كمتغيرات ضابطة. حيث تبنت الدراسة نموذج خطي لحساب الربحية اعتماداً على هذه المتغيرات. وخلصت الدراسة إلى العديد من النتائج كان أهمها: وجود أثر عكسي ذو دلالة إحصائية عند مستوى الدلالة (α≤ 0.05) لمعدل التضخم على ربحية البنوك الإسلامية الأردنية مقاسة بمعدل العائد على حقوق الملكية, ووجود أثر إيجابي ذو دلالة إحصائية عند مستوى الدلالة (α≤ 0.05) لمعدل التضخم على ربحية البنوك الإسلامية الأردنية مقاسة بمؤشر السيولة والرافعة المالية وحجم البنك. ولم يتم إثبات وجود أم عدم وجود أثر ذو دلالة إحصائية عند مستوى الدلالة (α≤ 0.05) لمعدل التضخم على ربحية البنوك الإسلامية الأردنية مقاسة بمؤشر قوة السوق لاستبعاد هذا المؤشر من الدراسة لوجود ترابط خطي متعدد كبير بين قوة السوق وحجم البنك. أوصت الدراسة بضرورة وضع استراتيجيات أفضل لمواجهة تأثير التضخم للسماح بأرباح مستدامة وجذب المستثمرين ومنع تصفيتها وذلك من خلال خلق توازن بين مختلف المصادر النقدية للتقليل من المخاطر المختلفة خاصة مخاطر التضخم لزيادة ربحيتها وبالتالي الحفاظ على استثماراتها. The study aimed to demonstrate the impact of inflation risks on the profitability of Jordanian Islamic banks. The study adopted the descriptive analytical approach and the standard approach as a survey on Jordanian Islamic banks during the period 2015-2019, using linear and multiple regression analysis, correlation analysis and significance tests. The study was conducted on all the three Jordanian Islamic banks: (Jordan Islamic Bank for Finance and Investment, Arab Islamic International Bank, and Safwa Islamic Bank). To achieve the objective of the study, the average inflation rate index was adopted as an independent variable and the return on equity (ROE) index to measure profitability as a dependent variable, and the liquidity index, financial leverage, market strength, and bank size were adopted as control variables. The study adopted a linear model to calculate profitability depending on these variables. The study concluded that there is an adverse statistical significance impact at the level of (α≤ 0.05) of the inflation rate on the profitability of Jordanian Islamic banks measured by the rate of return on equity (ROE), a positive statistical significance impact at the level of (α≤ 0.05) of Inflation rate based on the profitability of Jordanian Islamic banks, measured by the liquidity index, financial leverage, and bank size. The presence or absence of a statistically significant impact at the level of (α≤ 0.05) of the inflation rate on the profitability of Jordanian Islamic banks as measured by the market strength index has not been demonstrated and has been excluded from the study due to the existence of a large multiple linear correlation between market strength and the size of the bank. The study recommended that there is a necessity of developing better strategies to confront the impact of inflation to allow sustainable profits, attract investors and prevent their liquidation, by creating a balance between the various monetary sources to reduce the various risks, especially the risks of inflation, to increase its profitability and thus, preserve its investments.
The Impact of Risks of Inflation on the Profitability of Jordanian Islamic Banks
مقال
Keywords: التضخم ; الربحية ; ROE ; البن ; ك الأسلامية الأردنية